A Returns-Based Representation of Earnings Quality - Ecker, Frank; Francis, Jennifer; Kim, Irene; Olsson, Per M.; Schipper, Katherine (The Accounting Review, 2006)
We examine the properties of a returns-based representation of earnings quality, estimated from firm-specific asset-pricing regressions augmented by an earnings quality mimicking factor. The coefficient on the earnings quality factor (the “e-loading”) captures the sensitivity of the firm's returns to earnings quality in a given year or quarter, analogous to beta as a measure of the sensitivity of returns to market movements. Relative to other proxies for earnings quality, e-loadings can be calculated for larger samples of firms and can be estimated for shorter intervals at any point in time. Along all dimensions examined, we find that e-loadings perform well in capturing notions of earnings quality.